Methods of the investigation of dynamical systems with pulse effect and “mortal” dynamical systems - Urmanchev, V.I. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The notions of dynamical systems with impulse action and “mortal” dynamical systems are introduced. Their connection with the idealizations of ordinary dynamical systems is considered. General methods for the investigation of these systems are worked out.